Case Study - People Vs. Profit : An Ethical Dilemma - Zaleha Yazid; Farhana Sidek; Khairul Akmaliah Adham (Universiti Sains Islam Malaysia, 2024)
SYNOPSIS This case is about ethical behavior and reasoning and the framework that govern the Islamic business ethics.